GENE-45. DISSECTING THE DRIVERS OF ADULT H3K27M-GLIOMAS AT THE SINGLE-CELL LEVEL. (11th November 2019) - Liu, Ilon; Avihai, Byron; Gojo, Johannes; Ligon, Keith; Czech, Thomas; Slavc, Irene; Kleinman, Claudia; Jabado, Nada; Filbin, Mariella
Abstract: Diffuse midline gliomas are characterized by a lysine27-to-methionine mutation in histone H3 (H3K27M-glioma) and represent a highly aggressive molecular entity of high-grade gliomas. These mutations have primarily been described in children, but are also increasingly recognized in adults. In pediatric H3K27M-gliomas, the transcriptional architecture and cellular composition have been studied at the single-cell level. Data suggest that these tumors arise through malignant transformation of a glial progenitor during a specific neurodevelopmental time window. On the other hand, little is known about the architecture and cellular context of adult H3K27M-gliomas, and it remains to be elucidated whether they are driven by the same or by distinct oncogenic programs as their pediatric counterparts. Here, we utilize single-cell transcriptomics to characterize the transcriptional landscape of five H3K27M-gliomas from adult patients aged 22 to 56 years (median 33 years). We describe the specific cellular and microenvironmental architecture of the adult tumors, which comprises distinct populations of cancer and normal cells. We contrast our findings to 12 location-matched pediatric H3K27M-tumors from patients aged 2.5 to 15 years (median 8 years) to identify features related to tumorigenesis and developmental context in light of the shared hallmark H3K27M mutation. Our preliminary data indicate shared gene expression programs between adult and pediatric tumors. However, we find significant differences in the composition of the immune compartment as well as less pronounced differentiation programs in the adult tumors. Our findings provide an unprecedented insight into the composition of adult H3K27M-gliomas and advance our understanding of this molecular tumor class.